THE INFLUENCE OF SOCIAL AND LIFESTYLE FACTORS ON PRODUCT PURCHASE DECISIONS AT CENTRAL FASHION KISARAN, ASAHAN, NORTH SUMATERA - TENGKU SYARIFAH; DAILAMI; HENI SUBAGIHARTI (CV KULTURA DIGITAL MEDIA, 2020)
This study aims to determine and analyze how much influence social factors and lifestyle on product purchasing decisions on the Central Fashion Range of Asahan. The study was conducted on 50 samples, where the determination of the sample used was accidental sampling. The results showed that social factors (X1), and lifestyle factors (X2) together had a positive influence on purchasing decisions on the Central Fashion Range. This can be seen from the results of the regression equation, where Y = 0.336 + 0.280 X1 + 0.286 X2 + e. Based on the results of the F test it can be seen that social factors and lifestyle factors have a significant influence on product purchasing decisions with a significance level of 0,000 or 0%. Based on a partial test (t), all variables have a significant influence on purchasing decisions for fasion products with a significant level for social factors of 4.199 or 4.19%, and lifestyle factors of 4.523 or 4.52%; Of the two variables that influence purchasing decisions for Central Fashion Range Asahan products, the most dominant variable is the lifestyle factor variable because it has a tcount of 4.523 greater than the social factor, with the required significance.